The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/agronomy10091442
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Effects on Yield and Some Consumer Important Fruit Quality Parameters of Eggplant cv. ‘Madonna’ under Protected Cultivation

Abstract: This study aimed to investigate the effect of different rootstocks on the yield and quality of eggplant cv. ‘Madonna’ in soilless pot culture in an unheated polyethylene greenhouse. The eggplant was grafted onto several rootstocks, including tomato rootstocks Optifort (O) and Emperador (E), and four Solanum rootstocks; Solanum grandiflorum × Solanum melongena (SH), Solanum torvum (ST), Solanum melongena × Solanum integrifolium (SI), and Solanum integrifolium (A) compared with self-grafted (SG) and self-rooted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Sabatino and co-workers [12] demonstrated that grafting eggplant onto S. torvum or S. paniculatum boosted significantly the synthesis and concentration of antioxidant molecules, such as ascorbic and chlorogenic acids, and reduced the accumulation of glycoalkaloids. Similar results were also observed in eggplant grafted onto two tomato (Emperador and Optifort) and four Solanum (S. torvum, S. integrifolium, S. grandiflorum × S. melongena and S. melongena × S. integrifolium) rootstocks, which resulted in higher consumer fruit quality parameters compared to non-grafted and self-grafted plants [13]. Particularly, greenhouse eggplant grafted onto tomato rootstocks exhibited the lowest pulp color difference and oxidation potential, while the sweetest taste during the sensory evaluation was recorded in eggplant fruits harvested from plants grafted onto S. torvum.…”
supporting
confidence: 76%
“…Sabatino and co-workers [12] demonstrated that grafting eggplant onto S. torvum or S. paniculatum boosted significantly the synthesis and concentration of antioxidant molecules, such as ascorbic and chlorogenic acids, and reduced the accumulation of glycoalkaloids. Similar results were also observed in eggplant grafted onto two tomato (Emperador and Optifort) and four Solanum (S. torvum, S. integrifolium, S. grandiflorum × S. melongena and S. melongena × S. integrifolium) rootstocks, which resulted in higher consumer fruit quality parameters compared to non-grafted and self-grafted plants [13]. Particularly, greenhouse eggplant grafted onto tomato rootstocks exhibited the lowest pulp color difference and oxidation potential, while the sweetest taste during the sensory evaluation was recorded in eggplant fruits harvested from plants grafted onto S. torvum.…”
supporting
confidence: 76%
“…Although, both productivity and quality of grafted vegetables may differ and be contradictory from the perspective of the grower and the consumer. Vegetable quality is defined primarily by characteristics such as texture, flavor (volatile aromas, acids, sugar) and the content of compounds that promote health (phenols, carotenoids, vitamins, minerals) or are harmful to health (nitrates, heavy metals and pesticides), all of which can be affected by the rootstock as a result of translocation of metabolites [ 76 , 77 ]. On the other hand, consumer demand determines the economic value and represents an essential aspect in the production of grafted vegetables [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable quality is defined primarily by characteristics such as texture, flavor (volatile aromas, acids, sugar) and the content of compounds that promote health (phenols, carotenoids, vitamins, minerals) or are harmful to health (nitrates, heavy metals and pesticides), all of which can be affected by the rootstock as a result of translocation of metabolites [ 76 , 77 ]. On the other hand, consumer demand determines the economic value and represents an essential aspect in the production of grafted vegetables [ 76 ]. [ 78 ]; concluded that abiotic stress improves certain quality attributes of harvested fruit, in selected wild selected rootstocks, which evidences an alternative to mitigate its undesirable impact.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies have been conducted to determine the impact of rootstocks on the plant growth, fruit yield, and quality of eggplants [18][19][20][21][22][23]. According to Wei et al [24], grafting eggplant cv.…”
Section: Introductionmentioning
confidence: 99%